Respuesta :

Whenever you have a function, think of it like a machine. When you insert, let's say, meat into a meat grinder, the grinder "transforms" the meat as its function and outputs ground beef as a result. Here's it's really no different. Our meat is -1 and our meat grinder is [tex] f(x)=x^2+1 [/tex]. Rather than making meat, though, our machine takes its input, squares it, then adds one. Now, let's insert -1 into our machine:

[tex] f(-1)=(-1)^2+1=1+1=2 [/tex]

Out function outputs 2 with an input of -1.

To evaluate this function for f(-1), plug -1 in for every x in the function.

f(x) = x² + 1 (given)

f(-1) = -1² + 1 (substitute)

f(-1) = 1 + 1 (square -1)

f(-1) = 2 (add)

Answer:

F(-1) = 2